The Role of Histone Methyltransferases and Long Non-coding RNAs in the Regulation of T Cell Fate Decisions - Gaballa, Joseph M.; Braga Neto, Manuel Bonfim; Ramos, Guilherme Piovezani; Bamidele, Adebowale O.; Gonzalez, Michelle M.; Sagstetter, Mary R.; Sarmento, Olga F.; Faubion, William A. (Frontiers in Immunology, 2018)
T cell lineage decisions are critical for the development of proper immune responses to pathogens as well as important for the resolution of inflammatory responses. This differentiation process relies on a combination of intrinsic and extrinsic factors converging upon epigenetic regulation of transcriptional networks relevant to specific T cell lineages. As these biochemical modifications represent therapeutic opportunities in cancer biology and autoimmunity, implications of writers and readers of epigenetic marks to immune cell differentiation and function are highly relevant. Given the ready adoption of histone methyltransferase inhibitors in the clinic, we focus this review on the role of three histone modifying complexes: PRC-1, PRC-2, and G9A in modulating T cell fate decisions. Furthermore, we explore the role of long non-coding RNAs in regulating these processes, and discuss recent advances and challenges of implementing epigenetic therapies into clinical practice.